Factors Affecting Adoption of Recommended Rice Cultivation Practices by Farmers of South Kerala - S, Shanila (Journal of Extension Education, 2025)
Rice is a fundamental staple crop and plays a significant role in agricultural production across the southern part of Kerala, India. Implementing recommended rice cultivation practices is essential for boosting yield, promoting sustainability, and enhancing the livelihoods of farmers. However, even with the scientifically proven practices developed by Kerala Agricultural University (KAU), the extent of adoption among farmers differs considerably. The present study was conducted in Thiruvananthapuram, Kollam, Alappuzha, Pathanamthitta, Kottayam, Ernakulam and Idukki districts to find out the factors affecting adoption of recommended rice cultivation practices by the farmers of South Kerala. A total of 105 respondents were selected from one panchayat of each of these seven districts. The extent of adoption of selected KAU technologies in rice varieties was found to be ‘medium’ among the majority of farmers. The results of the correlation analysis revealed that out of 11 independent variables selected for the study, three variables were positively and significantly related to the dependent variable adoption of recommended practices by rice farmers. The main factors that influence technology adoption of recommended practices were extension participation and achievement motivation followed by innovativeness.